Global Reset: The Role of Investment, Profitability, and Imperial Dynamics as Drivers of the Rise and Relative Decline of the United States, 1929–2019. (1st April 2021) - Dunford, Michael
Abstract : A new world order is taking shape as a result of the relative decline of the United States (US) and other Western economies. An important aspect of relative decline is a progressive secular slowing down of productivity growth. Another is the way US development has been shaped and to some extent offset by international resource transfers. To explain these phenomena, attention is paid to the role of profitability as a driver of productivity and investment and global hegemony as a driver of international resource transfers. Particular attention is paid to an empirical analysis of the profitability of the US corporate non-financial sector and the existence of a secular decline in profitability since the mid-1960s interrupted only by the upward phases of a series of shorter-term economic cycles. Attention is also paid to the role of financial investments and some of the international resource transfers that have shaped, offset, and contained relative economic decline. An analysis of these trends frame and explain epochal changes in the dynamics and map of uneven and combined development and the likelihood of a global reset as the centre of world development shifts to Asia and the Eurasian continent.